A randomized trial of catheters of different lengths to achieve right atrium versus superior vena cava placement for continuous renal replacement therapy - Morgan, D.; Ho, K.; Murray, C.; Davies, Hugh; Louw, J. (2012)
Background: The aim was to assess whether inserting a longer soft silicone short-term dialysis catheter targeting tip placement in the right atrium could improve dialyzer circuit life span compared with inserting a shorter dialysis catheter targeting tip placement in the superior vena cava. Study Design: Randomized unblinded controlled study. Setting & Participants: A tertiary multidisciplinary intensive care unit enrolling 100 critically ill patients requiring continuous renal replacement therapy (CRRT). Intervention: Placement of longer (20-24 cm) versus shorter dialysis catheters (15-20 cm) within one of the major thoracic veins for initiation of CRRT. Outcomes: The primary study outcome was duration of dialysis circuit life span. Secondary outcomes included delivered daily dialysis dose, incidence and cause of CRRT circuit failure, complications potentially related to the position of the short-term dialysis catheter, mortality, and patient length of stay.Results: Placing the longer dialysis catheters was associated with an increased average dialyzer life span of 6.5 hours (24 hours [25th-75th percentile, 11-32] vs 17.5 hours [25th-75th percentile, 8-23]; P = 0.001), improved delivered daily dialysis dose (91% [25th-75th percentile, 85%-100%] vs 81% [25th-75th percentile, 72%-97%]; < 0.001), and reduced number of dialyzers clotted (2.3 vs 3.6; P = 0.04) or circuits taken down due to vascular access problem (0.19 vs 0.53; P = 0.04) per patient compared with placing shorter dialysis catheters. The incidence of atrial arrhythmias was similar between groups (28% vs 21%; P = 0.6) and the only mechanical complication was the malposition of one dialysis catheter tip in the longer dialysis catheter group. Limitations: Single-center study design. Conclusions: The use of longer soft silicone short-term dialysis catheters targeting right atrial placement appeared to be safe and could improve dialyzer life span and daily dialysis dose of CRRT delivered compared with the use of shorter catheters targeting superior vena cava placement.